Dissecting Immunosuppressive Cell Communication Patterns Reveals JunB Proto-Oncogene (JUNB) Shaping a Non-Inflamed Tumor Microenvironment - Chen, Hualin; Chen, Gang (Frontiers in Genetics, 2022)
Immunosuppressive cell interactions are responsible for the tumor progression and metastasis as well as anti-tumor immune dysfunction. However, the communication pattern remains unclear. We integrated single-cell RNA-seq datasets and identified four types of immunosuppressive cells including cancer-associated fibroblasts (CAFs), tumor-associated macrophages (TAMs), tumor-associated neutrophils (TANs), and regulatory T cells (Tregs). Based on gene regulatory networks and the interactions of immunosuppressive cells and tumor cells, we constructed an intercellular communication signature that divided the pan-cancer TME into two clusters with distinct immunological features and different responses to immunotherapy. In combination with pathway analysis, JUNB was identified as the hub gene of the immunosuppressive TME and it designed a non-inflamed TME of bladder cancer according to evidences that JUNB was negatively correlated with immunomodulators, chemokines, MHC molecules, immune cell infiltration abundances, anti-cancer immune response, and immune checkpoints inhibitors. Besides, JUNB may predict an unfavorable response to immunotherapy. The signaling network of the four types of cells demonstrated the dominant roles of CAFs and TAMs in the TME. Further investigation uncovered the complement signal was highly activated in the interactions between subpopulations of the inflammatory phenotype of CAFs and TAMs. Functional experiments further supported that CAFs promoted tumor proliferation by JUNB. Collectively, our findings shed insights into the immunosuppressive TME communication network and provided potential therapeutic targets.